Investigation of physico-chemical characteristics and associated CCN activation for different combustion sources through Chamber experiment approach. (1st December 2021) - Mukherjee, S.; Anil Kumar, V.; Patil, R.D.; Meena, G.S.; Buchunde, P.; Waghmare, V.; Deshmukh, S.; Dhavale, V.; Ray, A.; Panicker, A.S.; Sonbawne, S.M.; Safai, P.D.; et al.
Abstract: The aerosol physico-chemical properties along with their CCN activation characteristics were studied for different combustion source types such as Diesel Generator (DG), wood, leaf, charcoal, grass and cow dung through chamber-based experiment. Aethalometer (AE-33), High resolution time-of-flight aerosol mass spectrometer (HR-TOF-AMS), scanning mobility particle sizer (SMPS) and cloud condensation nuclei (CCN) counter were connected in line to derive the absorption properties, chemical composition, size distribution and CCN number concentrations respectively. Angstrom absorption exponent (AAE) and Angstrom absorption exponent ratio (AAER) were estimated utilizing the Aethalometer data. The analysis reveals that the DG emission was associated with the lowest AAE value (0.92) and the AAE value was highest for cow dung emissions (2.15). AAER, a ratio of AAE at longer wavelengths (660–950 nm) to smaller wavelengths (370-660 nm), showed value < 1 for most of biomass burning types, whereas, the AAER value was >1 for DG emission. The chemical composition data reveals that the organics contribute more than 90% to most of the combustion sources except charcoal, for which the organic contribution was only 78%. High-resolution data analysis reveals that leaf burning was associated with the highest f 44 fraction indicating the emitted organic aerosols contain more oxygen. The chemical composition derived hygroscopicity parameter (κ) was estimated to be highest for charcoal emissions and lowest for diesel and cooking emissions. Hygroscopicity parameter (κ) was also evaluated utilizing CCN and SMPS data. The CCN activation and size distribution analysis revealed that the CCN activation of cow dung was highest at 0.1% and 0.3% SS, this is associated with the higher geometric mean diameter (GMD) of emitted aerosols, indicating the importance of size compared to the chemical composition. The activation fraction of charcoal emission was found to be higher than DG emission in these super-saturations, indicating the importance of hygroscopicity in addition to size for governing the CCN activation when the GMD is on the lower side. Graphical abstract: Image 1 Highlights: Physico-chemical characteristics of different combustion types were studied. DG emitted aerosols are highly hydrophobic in nature. The estimated hygroscopicity was found to be highest for charcoal emission. Cow-dung emits larger size aerosols which activates faster at lower supersaturations. Chemical composition is crucial when emitted aerosol are in lower size regimes.